RELEASE OF NUCLEIC ACIDS FROM THE INTERNAL ORGANS OF RODENTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
Studies on the isolation of nucleic acids from the internal organs of rodents werecarried out at the Institute of Biotechnology of the National Academy of Sciences of the KyrgyzRepublic in the laboratory of biotechnology and nutrition. The aim of this study was to studymethods for the isolation of nucleic acids from the internal organs of rodents. In the course of theresearch, the methods of DNA and RNA isolation from different samples of biological objectswere mastered. The method of qualitative and quantitative accounting of DNA and RNA isolatedfrom samples was carried out using a Nano Drop 2000 spectrophotometer. According to the resultsof the study, 25 DNA samples and 24 RNA samples had admissible concentrations 84,3 – 630,5 9,which made it possible to use them for further research.
Keywords: DNA and RNA of biological objects; qualitative and quantitative accounting.